Respuesta :

Answers:

f(3) = -7

g(-2) = 1

h(4) = 7

============================================================

Work Shown:

[tex]f(x) = 8-5x\\\\f(3) = 8-5(3)\\\\f(3) = 8-15\\\\f(3) = -7\\\\[/tex]

------------------

[tex]g(x) = 3x+7\\\\g(-2) = 3(-2)+7\\\\g(-2) = -6+7\\\\g(-2) = 1\\\\[/tex]

------------------

[tex]h(x) = \frac{x}{2}+5\\\\h(4) = \frac{4}{2}+5\\\\h(4) = 2+5\\\\h(4) = 7\\\\[/tex]

As the steps above show, we replace x with the input value in question. Then we follow the order of operations (PEMDAS) to simplify.

Answer:

f(3) = -7

g(-2) = 1

h(4) = 7

Step-by-step explanation:

Given f(x) = 8 - 5x

→ f(3) means substitute x = 3 into the function:

⇒ f(3) = 8 - 5(3)

          = 8 - 15

          = -7

Given g(x) = 3x + 7

→ g(-2) means substitute x = -2 into the function:

⇒ g(-2) = 3(-2) + 7

            = -6 + 7

            = 1

Given h(x) = x/2 + 5

→ h(4) means substitute x = 4 into the function:

⇒ h(4) = 4/2 + 5

          = 2 + 5

          = 7

ACCESS MORE